Defect Passivation for Kesterite CZTSSe Solar Cells via In Situ Al2O3 Incorporation into the Bulk CZTSSe Absorber. Issue 4 (8th January 2022) - Lee, Taeseon; Hamim Sharif, Md; Enkhbayar, Enkhjargal; Enkhbat, Temujin; Salahuddin Mina, Md; Kim, JunHo
Abstract : A method for in situ Al2 O3 incorporation into a Cu2 ZnSn(S, Se)4 (CZTSSe) absorber and its effect on solar cell performance is reported. Al2 O3 ‐incorporated CZTSSe films can be prepared by spraying a precursor solution containing Al metal salt dissolved together with Cu, Zn, and Sn metal salts and thiourea. X‐ray photoemission spectroscopy (XPS) and field‐emission transmission electron microscopy (FESEM) reveal the existence of an Al2 O3 phase in the CZTSSe film. X‐ray diffraction (XRD) and Raman spectroscopy indicate that Al2 O3 incorporation (Al: 0%–2%) does not have a noticeable effect on the crystallization process through postselenization and does not change the lattice parameters of the selenized CZTSSe. However, optimal Al2 O3 incorporation is found to reduce the defect level and defect density, as confirmed by various characterization methods, such as 442 nm Raman spectroscopy, photoluminescence, admittance spectroscopy, and temperature‐dependent current density measurements. In addition, Al2 O3 incorporation reduces the Urbach energy and back‐contact barrier height. Al2 O3 incorporation is found to induce enhancement of Na and O concentrations in the absorber, which facilitates defect passivation effects. Owing to the observed beneficial effects of Al2 O3 incorporation, the device performance is significantly enhanced, achieving a maximum power conversion efficiency of 11.76%. Abstract : By in situ Al2 O3 incorporation, Na and O concentrations in a kesterite absorber are increased, which facilitates defect passivations both at the surface and at the grain boundary. Due to the passivation effects, the power conversion efficiency of the CZTSSe solar cell is increased up to 11.76%.